ON THE ANALYSIS OF LEXICAL UNITS RELATED TO THE FUNERAL CEREMONY IN UZBEK AND GERMAN LANGUAGES (Scientific journal of the Fergana State University, 2023)
In this article, the lexical units related to the funeral ceremony in Uzbek and German languages ​​are dafn, aza, maraka, janoza, tazia, member, deceased, relatives of the deceased, burial, cemetery, priest, music, mourning, cry, speech, prayer, basket with petals, white balloons, white doves, sympathy, consolation, farewell, flowers and wreaths, Uzbek and German mourning clothes, mourning ceremonies, place of mourning names, etc. are thoroughly researched. Also distinctive features of the above mentioned lexical units, similarities and differences are revealed.